Financial and Economic Drivers of Ecological Footprint: a Panel Quantile Regression Analysis of the EU - Serap Vurur; Munevvere Yildiz; Letife Ozdemir (Statistika: Statistics and Economy Journal)
The European Union (EU), as a signatory to the Paris Climate Agreement, aims to take on a global leadership role in sustainable environmental initiatives. This study explores the contribution of economic and financial developments to environmental sustainability in EU member states with successful environmental policies. The impacts of economic growth, financial development, and foreign direct investments on the ecological footprint are examined for 16 EU member states. Data from 1990–2021 is analysed using panel quantile regression and the Dumitrescu-Hurlin causality test. According to the results, the overall impact of economic growth and financial development on the Ecological Footprint is positive. Additionally, foreign direct investments contribute to an increase in ecological footprint. According to the causality test results, economic growth and ecological footprint mutually influence each other. There is a unidirectional causality from financial development and foreign direct investments to ecological footprint. Implementing financial policies directed towards eco-friendly technologies in EU member states will positively impact environmental sustainability.